Seni Sebagai Media Dakwah (Analisis Pemikiran Dakwah Ahmad Rifa’I dalam Kitab Ri’āyah al-Himmah) - Sri Widyastri (FDIK IAIN Padangsidimpuan, 2022)
This study aims to explore and analyze the legal classification of the prohibition of art according to KH. Ahmad Rifa'i. This research was conducted to dig up information on how art is used as a medium for preaching KH. Ahmad Rifa'i. In addition, this research is expected to reduce or even remove bad stigmas about KH students. Ahmad Rifa'i, who was later called Rifa'iyah, had been spread throughout the community. This study uses a qualitative method. The subjects in this study were residents of Rifa'iyah, while the object studied was the da'wah of KH. Ahmad Rifa'i. Methods of data collection using interviews, observation, and literature study. The results of this study indicate that art is prohibited if it violates religious law according to salaf scholars (not Khalaf). Still, if it does not violate the law then the prohibition of art can be revoked. At the same time, art is used as a medium of propaganda KH. Ahmad Rifa'I is a poem or a stanza. This can be seen in the works of KH. Ahmad Rifa'I has been recorded in several books based on the material discussed. Keywords: Da'wah, Art, and Ahmad Rifa'i